The effectiveness of service quality by Jabatan Agama Islam Wilayah Persekutuan (JAWI) towards customer satisfaction / Mohamad Idham Md Razak … [et al.] - Md Razak, Mohamad Idham; Mohammad Hamzah, Mohd Hafiz; Supir, Hafifi; Yaacob, Noor Junaini Arwin; Mohd Rodzi, Siti Nurul Aini (Division of Research and Industry Linkages, UiTM Melaka, 2014)
The purpose of this research is to identify the relationship between service quality and customer satisfaction. It includes the dimensions of service qualify which are tangible, reliability, responsive, assurance and empathy. Then, the problem statement regarding on this study is the limited budget to improve the management by allocating the budget to make the seminar for the employee to improve the performance and knowledge especially for the receptionist and public relation staff. Then, the problem is lack in providing complete facilities for the employees and the relationship with the supplier. The objectives of this study are to study the level of customer satisfaction in Jabatan Agama Islam Wilayah Persekutuan (JAWI), to study the relationship between assurance, responsiveness, tangible, empathy and reliability toward customer satisfaction, to study the most variable influence customer satisfaction in Jabatan Agama Islam Wilayah Persekutuan (JAWI) and to study the alternatives to improve customer satisfaction on Jabatan Agama Islam Wilayah Persekutuan (JAWI). The theoretical framework is adapted from Muslim Amin, Zaidi Isa (2008) which is appropriate for this study. Non probability research design is use and the respondents were chosen by using convenience sampling in conducting this study. The 50 respondents have chosen to distribute the questionnaires to gain the information and feedback. Lastly, the finding obtained is significant which is there is a positive relationship of between the service quality and customer satisfaction at Jabatan Agama Islam Wilayah Persekutuan.